Determination of Organizational and Economic Determinants of the Current State and Development Trends of Agricultural Producers in Poland and Ukraine - Diana Shelenko; Arkadiusz Kijek; Oleksandr Shpykuliak (Vasyl Stefanyk Precarpathian National University, 2023)
The experience of highly developed countries proves that agricultural producers are one of the stabilizing factors of the socio-economic relations of states as a whole. In the context of effective management of agricultural producers in Ukraine and Poland, it is important to find out the features and trends of their modern development. A number of tools have been involved to stimulate the development of agriculture, which include: improvement of institutional support; infrastructure development of rural areas; implementation of financial instruments for the development of agriculture; provision of personnel at agricultural producers. The subject of our economic research interests is the characterization of organizational and economic determinants and a comparison of the development trends of agricultural production in Poland and Ukraine in the context of modern food security challenges. The results of the calculations can be taken into account for operational and strategic planning of the behaviour of agricultural producers. The aim of the investigation is to outline the development trends of agricultural producers in Ukraine and Poland and to develop approaches to ensure their effective functioning. A systematic approach to the study of conditions and factors that comprehensively affect the development of agricultural producers has been applied. The research uses a comparative analysis of the main economic indicators of the activity of agricultural producers in Ukraine and Poland. A comprehensive approach allowed us to conduct a study of the main indicators of the activity of agricultural producers with the inclusion in their production activity of the entire set of social and production components. The study confirms the better performance of the Polish agricultural sector than the Ukrainian one in 2010-2020. It suggests potential benefits from the use of Polish experiences by Ukrainian producers. Integration processes are characteristic of all sectors of the economy, but in agriculture, based on the specifics of the sector, and as the experience of enterprises in Poland and the Lublin Voivodeship shows, provide positive results, both for agricultural producers themselves and for society as a whole.